DETERMINANT FACTORS FOR CENTRAL LINE-ASSOCIATED BLOOD STREAM INFECTIONS (CLABSI) IN NEONATES: Faktor Determinan Central Line-Associated Blood Stream Infections (CLABSI) Pada Neonatus - Nihar, Mahdiyyah Husna; Martini, Santi; Husada, Dominicus (Universitas Airlangga, 2025)
Background: CLABSI accounts for 70% of all hospitalized bloodstream infections, especially in premature infants. CLABSI in neonates can compromise the immune system and future quality of life. Purpose: This study aims to identify determinant factors associated with CLABSI in neonates. Methods: This research was a scoping review study of three international databases namely Science Direct, PubMed, and ProQuest from January 2021-April 2024. Keyword selection refers to PCC (Populations, Concepts, Categories), with the keywords used